A case of angiomatoid epithelioid sarcoma mimicking an epithelioid vascular neoplasm - Lai, Shau Kong; Tan, Ling Tze; Tan, Lii Jye; Koh, Cai Ping; Yahaya, Balqis; Hussin, Huzlinda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Epithelioid sarcoma is a rare but aggressive soft tissue sarcoma that presents a significant diagnostic and manage- ment challenge to clinicians. We report a 31-year-old female who presented with a non-healing ulcer of three years’ duration on her left thumb after a burn. Examination revealed an ulcerative tumour invading the bone with areas of haemorrhage. Microscopic examination showed an epithelioid neoplasm with central necrosis. The neoplastic cells formed dyscohesive sheets, slit-like channels, and pseudovascular spaces. Erythrocytes were frequently observed in these areas. The neoplastic malignant cells were diffusely positive for cytokeratin AE1/AE3, EMA, vimentin, Fli-1; while focally positive for CD34 and CD31. The morphology and immunophenotype overlap with a vascular neo- plasm. Additional immunohistochemical stain revealed loss of SMARCB1/INI1 expression supporting the diagnosis of epithelioid sarcoma of distal type, angiomatoid variant. We present a distinctive case of angiomatoid epithelioid sarcoma that developed in a burn ulcer and highlight pathological characteristics that distinguish it from epithelioid vascular neoplasms.